The fine penalty nature and its applicability to legal persons and similar entities - LOPES, Manuel (Revista Jurídica Portucalense, 2023)
The crisis of the penal system and the autonomy of the property reinforced the penalty of fine. The corporation was strengthened as a concrete functional organization of capital and work. Core generator of criminal charge capable of action and guilt, objectionable behaviour, and offensive protected harm principle or social danger. Punishable with reference to the penalty of imprisonment and with uniformity of the days of fine in the type. The penalty of fine returned genuine criminal penalty related to ethical-normative devaluation, aided by binomial reference/uniformity, by the constitutive of distinction of the penalty of fine and disclosure of two aspects: extrinsic and intrinsic. Applicable to legal entities for impossibility of detention.